The own-wage elasticity of labor demand: A meta-regression analysis - Andreas Lichter; Andreas Peichl; Sebastian Siegloch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Firms' labor demand responses to wage changes are of key interest in empirical research and policy analysis. However, despite extensive research, estimates of labor demand elasticities remain subject to considerable heterogeneity. In this paper, we conduct a comprehensive meta-regression analysis to re-assess the empirical literature on labor demand elasticities. Building on 942 elasticity estimates from 105 different studies, we identify sources of variation in the absolute value of this elasticity. Heterogeneity due to the theoretical and empirical speci cation of the labor demand model, di fferent datasets used or sectors and countries considered explains more than 80% of the variation in the estimates. We further find substantial evidence for the presence of publication selection bias, as estimates of the own-wage elasticity of labor demand are upwardly inflated.
urn:nbn:de:bsz:180-madoc-361205
Keywords: J23; C10; C83; 330; labor demand; wage elasticity; meta-analysis